The economics of professional team sports - Downward, Paul, 1964-; Dawson, Alistair, 1940- (Routledge, 2000)
Do dominant teams kill public interest in professional sports? Do spectators relish close contest and unpredictable results? Are sports stars overpaid? Will recent changes to sports broadcasting undermine the traditional organisation of professional team sports? To address these, and other issues, this text offers a survey of the economic literature on sporting leagues, the demand for professional team sports and the players' labour market. Amongst the topics discussed are the US system of franchising and draft picks and the chances of their being adopted elsewhere, the implications of player strikes, the onset of pay-per-view and digital television, and the relatively new notion that sport is a business like any other.